2009
DOI: 10.1021/jp910227x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Incorporation of Au Nanoparticles into Polymer/Fullerene Solar Cells

Abstract: The addition of small amounts of dodecylamine-capped Au nanoparticles into the active layer of organic bulk heterojunction solar cells consisting of poly(3-octylthiophene) (P3OT) and C(60) was recently suggested to have a positive impact on device performance due to improved electron transport. This issue was systematically further investigated in the present work. Different strategies to incorporate colloidally prepared Au nanoparticles with a narrow size distribution into organic solar cells with the more co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
133
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(140 citation statements)
references
References 48 publications
7
133
0
Order By: Relevance
“…Some functional groups in the ligand may also provide localized states. Topp et al 12 had previously shown that gold nanoparticles encapsulated with different ligands (that is, with dodecylamine, pyridine, and so on) all had detrimental effects on the PCE of P3HT:PCBM OSCs. There is still a lack of understanding on how the capping ligands and particle size affect the net trapping rate.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Some functional groups in the ligand may also provide localized states. Topp et al 12 had previously shown that gold nanoparticles encapsulated with different ligands (that is, with dodecylamine, pyridine, and so on) all had detrimental effects on the PCE of P3HT:PCBM OSCs. There is still a lack of understanding on how the capping ligands and particle size affect the net trapping rate.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, all these issues may be resolvable through a prudent choice of the constituents and careful optimization of the device. From the analysis of our experimental results and careful comparison with the literature reports [8][9][10][11][12][13] , we can identify several key factors/ considerations for the design of hybrid plasmonic OSCs.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations